Enhancing Primary School Students’ Argumentative Speaking Skills through Collective Reflection-Based Argumentation Mapping - Zahrani, Salsabila Syafa'; Kharisma, Adib Jasni; Sagala, Rakhmat Wahyudin (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the effectiveness of Collective Reflection-Based Argumentation Mapping (CR-AM) in enhancing argumentative speaking skills among primary school students. Conducted with 20 sixth-grade students at Anuban Ob-Om School in Southern Thailand, the research employed a Classroom Action Research (CAR) approach over two cycles, with data collected through pre-tests, post-tests, and observations. The assessments of students' speaking skills, conducted by pre-test and post-test evaluations, demonstrated a substantial enhancement in average speaking scores, rising from 52.75 to 70.25, with all students achieving the minimum mastery criterion. Observational data revealed elevated levels of student involvement and participation during collective reflection activities, underscoring the advantages of collaborative learning. The findings show that CR-AM effectively fosters essential language skills, preparing students for meaningful communication and critical thinking.